Analisis Faktor Faktor Yang Mempengaruhi Underpricing Saham pada Perusahaan Yang Melakukan Initial Public Offering (IPO) di BEI Periode 2019-2021 (Studi Kasus pada Emiten Sektor Barang Konsumsi Primer) (International Forum of Researchers and Lecturers, 2023)
This study aims to analyze the factors that influence stock underpricing of IPO companies on the IDX in the primary consumer goods sector. The population in this study were 34 IPO companies in the primary consumer goods sector. This research is a quantitative research using primary data obtained from the official idx website. The statistical data value analysis technique used in this study is multiple linear regression. The results of this study indicate that company age, underwriter reputation and auditor reputation have no significant effect on underpricing.The results of this research analysis show that there are 2 influential variables, namely the firm age variable which has a significant value of 0.027 (<0.05). the Underwriter's Reputation variable has a Significant value of 0.018 (<0.05. And 1 variable that has no effect, namely the Auditor's Reputation variable has a Significant value of 0.238 (<0.05).